Water-soluble dopamine-based polymers for photoacoustic imaging. Issue 28 (11th February 2015) - Repenko, Tatjana; Fokong, Stanley; De Laporte, Laura; Go, Dennis; Kiessling, Fabian; Lammers, Twan; Kuehne, Alexander J. C.
Abstract : Here we present a facile synthetic method yielding a linear form of polydopamine via Kumada-coupling, which can be converted into water-soluble melanin, generating high contrast in photoacoustic imaging. Abstract : Here we present a facile synthetic method yielding a linear form of polydopamine via Kumada-coupling, which can be converted into water-soluble melanin, generating high contrast in photoacoustic imaging.